Design and Validation of an Open-Hardware Print-Head for Bioprinting Application. (2015) - De Maria, Carmelo; Ferrari, Laura; Montemurro, Francesca; Vozzi, Federico; Guerrazzi, Ilenia; Boland, Thomas; Vozzi, Giovanni
Abstract: In the last decades drop-on-demand inkjet technology played an increasing role in industrial and medical applications. This is due to the ability to deposit a small amount of material in precisely defined position. In the field of Biofabrication, inkjet printers are used to build 2D and 3D scaffolds and gels with biological molecules, including living cells. Several works, including seminal papers on inkjet bioprinting, were carried out with modified office printers. These printers have fixed structural characteristics and operating size, especially on the print-head, limiting the range of materials that can be dispensed. The aim of the present work is the design and fabrication of an open-source piezoelectric inkjet print-head, optimized for the bioprinting field. This low-cost, reproducible, reliable, versatile and biocompatible device will enable various research laboratories to work with a shared device; the open source allowing for parts to be modified to suit specific needs. The design was carried out by Finite Element (FE) modelling of the piezoelectric, mechanical, fluid dynamics and their coupling. The design was optimized for shear rate, which we minimized in order to be able to print cells. The mechanical frame of the printer was designed and built using a low-cost 3D printer. The nozzle plate was fabricated from a polycarbonate disc coated with biocompatible silicone, to increase the hydrophobicity of the outer surface of the disc, preventing ink adhesion on the edge of the nozzle; the refilling system, and the electronic control were also part of the project and will be freely available to download. The FE models were validated with ad-hoc experiments, printing water, gelatin solution, and cell culture media, by modulating the wave power in amplitude, frequency and duty cycle. The tests showed a large working window both respect to viscosity and to surface tension. Finally Human Skin Fibroblasts (ATCC-CRL- 2522, Teddington UK), suspended in culture media, were printed. Cell viability, assessed by CellTiter-Blue and LIVE / DEAD tests, resulted comparable with the control, demonstrating the validity of the first open source piezoelectric inkjet print-head for biofabrication.